KONSEP PENDIDIKAN AKHLAK MENURUT HAJI ABDUL MALIK KARIM AMRULLAH (HAMKA) - Fuad Ahmad Riva’i (Al-Mubin, 2021)
Globalization had been brought many changes in every life society aspect all over the world, in Indonesia especially. Despite of positive effect, it also has brought a negative effect for youth life style and student behavior such as western culture that contaminated their life style, taken them to materialistic life, hedonism and free sex. Education college as a maker the next generation has important role to make them as excellent generation. For this aim moral education has implemented as solution to overcome these problems. Hamka is one of greatest Islamic scholar who was born in Indonesia. His thought got many appreciations from Indonesian people. As his widely knowledge so he could write many books in any discipline of science, especially in tasawuf and education. So that the writer try to research his thought in moral education, such as his concept of moral and its education characteristic. The approach used in this research was a library research by qualitative research. This research attempt to reconstruct systemically Hamka thought in moral education. The data collected was analyzed by using descriptive-analysis method. Descriptive method was used to explain the moral concept and moral education characteristic according to Hamka. The research results showed that moral according to Hamka is attitude or behavior of life, as because the training and costuming in doing of good deed, regularly became his character. Hamka’s concept of moral education based on values of tauhidullah, with it’s aim to reach the happiness by knowing of Allah (Marifatullah). And his scopes of moral education are religious moral, moral in society, and moral toward humankind. Where as process of moral education on Hamka thought must be done by training method and costuming, then the good pattern form teacher. As the subject of this moral education according to Hamka must pay attention the balance of physical education and spiritual education to get the goal of this moral education, that is the happiness.